SISTEM INFORMASI GEOGRAFIS LETAK STASIUN PENGISIAN BAHAN BAKAR UMUM DI PROVINSI GORONTALO - Farid, Farid; Jabbar, Asnia (Program Vokasi Universitas Negeri Gorontalo, 2024)
The aim of the research is to design a Geographic Information System Mapping Institute courses will be applied to the general oil of Gorontalo City. The method used in the study is descriptive, ie research that seeks to solve the existing problems systematically based on the existing data in a systematic, factual and accurate information on the facts, properties and relationships among phenomena oil and gas stations. The test system used is whitebox testing by selecting modules from the web to be converted into a flowchart and then flowgraph is calculated after CC (Cyclometic Complexity) and Blackbox testing to obtain the correct test results.